Comparative bionomics of four populations of Meccus longipennis (Hemiptera: Reduviidae: Triatominae) under laboratory conditions - Martínez-Ibarra, José Alejandro (Instituto Oswaldo Cruz, Ministério da Saúde, 2013)
The values of biological parameters related to the life cycles of four populations of Meccus longipennis (Reduviidae: Triatominae) were evaluated. Cohorts of each of the four studied populations from different geographical areas of Mexico were maintained under similar laboratory conditions and then compared. The population from El Saucito de Araujo was different from the other three studied populations, which could help explain the secondary importance of M. longipennis in the state of Chihuahua. This paper also supports the proposition that biological traits are important criteria for determining relationships between populations.